The role of online shopping service quality in e-retailing towards online shopping intention: Testing the moderation mechanism in UTAUT - Muhammad Amjad-ur-Rehman; Abdul Qayyum; Basharat Javed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
The purpose of this research study isto examine the influence of online shopping service quality on online shopping intention with the mediating role of online shopping drivers and the moderating role of offline brand trust. The authors collected the data from 167 university students across Pakistan. Structuralequation modeling was used to analysis the data usingAMOS.The results confirmed that online shopping service quality promotes online shopping intention, while online shopping drivers mediatedthe effect of online service quality on online shopping intention (the major contributions of the current study in the literature of online shopping intention). Furthermore, the results did not support the moderating role of offline brand trust on the relationship between online shopping drivers and online shopping intention. The authors took guidance from unified theory of acceptance and use of technology to explain the relationships among the constructs. The implications are further discussedat the end.
Keywords: 330; online shopping service quality; online shopping drivers; offline brand; e-retailing; trust; UTAUT; online shopping Intention